Overview of Health Behaviors Using Karo Traditional Medicine in Karo People in Medan City - Rosliana Karolina Manalu; Ridhoi Meilona Purba (Talenta Publisher, 2020)
This research discusses health behaviors in Karo people in Medan. The purpose of this study is to provide an overview of health behaviors using Karo traditional medicine in Karo people in Medan. This research is a descriptive research with a quantitative approach. The method used in data collection is to use a scale of health behavior based on 4 aspects that Notoatmodjo said are promotive, preventive, curative, and rehabilitative with a total of 140 research subjects. The results of this study show health behaviors using Karo traditional medicine are in the moderate category.